2021
DOI: 10.1002/ett.4400
|View full text |Cite
|
Sign up to set email alerts
|

A survey of applied machine learning techniques for optical orthogonal frequency division multiplexing based networks

Abstract: In this survey, we analyze the newest machine learning (ML) techniques for optical orthogonal frequency division multiplexing (O-OFDM)-based optical communications. ML has been proposed to mitigate channel and transceiver imperfections. For instance, ML can improve the signal quality under low modulation extinction ratio or can tackle both determinist and stochastic-induced nonlinearities such as parametric noise amplification in long-haul transmission. The proposed ML algorithms for O-OFDM can in particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 130 publications
(370 reference statements)
0
2
0
Order By: Relevance
“…In this paper, we have investigated a machine learning-based convolutional neural network model for optical communication networks to achieve high capacity, long distance, and multi-channel transmission. We have compared our results with conventional approaches as discussed in [9] to [17], and found that our model has superior performance in terms of bit error ratio, optical signal-to-noise ratio, spectral e ciency, and power e ciency. We have also studied the four-wave mixing nonlinear cause, which severely degrades the quality of the transmitted signal at the receiver side.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, we have investigated a machine learning-based convolutional neural network model for optical communication networks to achieve high capacity, long distance, and multi-channel transmission. We have compared our results with conventional approaches as discussed in [9] to [17], and found that our model has superior performance in terms of bit error ratio, optical signal-to-noise ratio, spectral e ciency, and power e ciency. We have also studied the four-wave mixing nonlinear cause, which severely degrades the quality of the transmitted signal at the receiver side.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, many methods were used for compensation the effects of FWM nonlinear cause and enhance the SE of large distance and multi-channel OCN. In reference [9], the newest ML techniques were analyzed for modern elastic OCN to improve multi-channel transmissions. The optical orthogonal frequency domain multiplexing (O-OFDM) is measured for OAN.…”
Section: Research Reviewmentioning
confidence: 99%